Geomorphic conditions and anthropogenic irrigation as drivers of CO2 and CH4 emissions in Heihe River - Zhiheng Du; Wenhan Hu; Hao Cui; Lei Wang; Jingfeng Liu; Fangping Yan; Rinat Manasypov; Changlian Tao; Renjun Wang; Jing Luo; Chuntan Han; Xiqiang Wang (Global and Planetary Change, 2026)

Transcriptomics and single cell sequencing revealed the important role of PPAR signaling pathway in zebrafish liver fibrosis induced by thioacetamide - Yilong Cui; Mula Na; Xinxin Zhang; Jie Wang; Lei Song; Qianxun Wang; Chi Feng; Xiaodong Hu; Jianhua Yu; Guiying Kang; Wu Dong; Jingfeng Yang (Environmental Pollution, 2026)

Turncoat? Native Nitrogen‐Fixing Legumes Facilitate Plant Invasion via Soil Microbes and Nitrogen Transfer - Zhenwei Xu; Warwick J. Allen; Linwei Wu; Menglong Liu; Yi Hu; Jingfeng Wang; Mingyan Li; Xiao Guo; Weihua Guo (Global Change Biology, 2026)
Nitrogen deposition often promotes plant invasions and can arise from multiple sources. However, it remains unclear whether native legumes facilitate invasive plants directly through biotic nitrogen transfer or indirectly via soil microbial mediation. It is also unknown how exogenous nitrogen addition influences these facilitative effects. To address these questions, we combined evidence from a greenhouse experiment and global meta‐analysis. The greenhouse experiment tested the effects of neighboring plants (a native nitrogen‐fixing legume Albizia julibrissin ; a native non‐nitrogen‐fixing legume Styphnolobium japonicum ; or a conspecific) on the growth of invasive Rhus typhina and its native congener R. chinensis . Within‐pot membrane treatments were used to obstruct microbial and nitrogen movement between focal and neighboring plants, with and without added nitrogen. The total biomass of invasive R. typhina increased when grown with the nitrogen‐fixing legume compared with conspecific neighbors, but not when grown with the non‐nitrogen‐fixing legume. Positive effects of the nitrogen‐fixing legume on R. typhina were suppressed when nitrogen transfer or soil microbial movement was obstructed by membranes. Exogenous nitrogen addition did not alter the growth of invasive R. typhina or its interactions with legumes. The biomass of native R. chinensis did not differ among neighboring plant treatments, indicating that facilitation by legumes favored the invasive species. The global meta‐analysis of 268 effect sizes from 46 studies of the effects of legumes on neighboring plants also revealed that native legumes enhanced invasive plants' performance. Together, our findings recognize nitrogen‐fixing legumes as overlooked facilitators of plant invasion, operating through both nutrient and microbial mediated pathways. These findings highlight a paradox in which native species can act as “turncoats,” accelerating invasion and reshaping plant communities under global change.

Mechanical behaviour of axially-loaded reinforced CGCC columns: Testing and numerical modelling - Ziming Hu; Jingfeng Wang; Fengqin Wang; Zhenqing Shi; Zhenyu Hu (Engineering Structures, 2026)

Editor's Note to “Remote sensing and modeling fusion for investigating the ecosystem water‑carbon coupling processes” [Sci. Total Environ. 697 (2019), 134064] - Pengcheng Sun; Yiping Wu; Jingfeng Xiao; Jinyu Hui; Jingyi Hu; Linjing Qiu (Science of The Total Environment, 2026)

Transcriptome and metabolome analyses revealed mechanisms underlying vernalization-induced bolting in two contrasting genotypes of cabbage (Brassica oleracea var. capitata) - Huiju Yang; Jingfeng Hu; Mingwei Chen; Mei Lan; Jiangming He (Journal of Plant Biochemistry and Biotechnology, 2025)

Mechanical analysis of eccentrically loaded SFRC columns reinforced by high-strength rebars: Testing and FE modelling - Ziming Hu; Jingfeng Wang; Qihan Shen; Beibei Li; Yong Liu (Engineering Structures, 2025)

Identification of carbon dioxide and methane emission characteristic across Heihe River, China - Wenhan Hu; Zhiheng Du; Lei Wang; Fangping Yan; Chuntan Han; Xiqiang Wang; Changlian Tao; Jingfeng Liu (Science of The Total Environment, 2025)

Edge-Based Dynamic Spatiotemporal Data Fusion on Smart Buoys for Intelligent Surveillance of Inland Waterways - Ruolan Zhang; Chenhui Zhao; Yu Liang; Jingfeng Hu; Mingyang Pan (Journal of Marine Science and Engineering, 2025)
Increasing vessel traffic in narrow, winding inland waterways has heightened the risk of accidents, driving the need for improved surveillance and management. This study addresses the challenge of real-time processing and synchronization of voluminous video and AIS data for effective waterway management. We developed a surveillance method utilizing smart buoys equipped with sensors and edge computing devices, enabling dynamic spatiotemporal data fusion. The integration of AIS data with advanced computer vision techniques for target detection allows for real-time traffic analysis and provides detailed navigational dynamics of vessels. The method employs an enhanced Long Short-Term Memory network for precise trajectory prediction of AIS data and a single-stage target detection model for video data analysis. Experimental results demonstrate significant improvements in ship detection accuracy and tracking precision, with an average position prediction error of approximately 1.5 m, which outperforms existing methods. Additionally, a novel regional division and a Kalman filter-based method for AIS and video data fusion were proposed, effectively resolving the issues of data sparsity and coordinate transformation robustness under complex waterway conditions. This approach substantially advances the precision and efficiency of waterway monitoring systems, providing a robust theoretical and practical framework for the intelligent supervision of inland waterways.

In situ construction of ion/electron conductive components via lithiation strategy enhancing cycling capability and initial Coulombic efficiency of Si anode - Jingfeng Cao; Xiang Yan; Dan Li; Liuyi Hu; Tiansheng Chen; Weiwei Gao; Wenlong Song; Xinhui Xia; Yang Xia; Wenkui Zhang; Hui Huang (Chemical Engineering Journal, 2025)

Microbial degradation of DOC released by the mixed culture of Crassostrea gigas and Undaria pinnatifida - Tian Hu; Jie Su; Kuishuang Shao; Shanshan Dong; Yuyang Xie; Yawen Wei; Hongxia Ming; Tingting Shi; Ge Guo; Jingfeng Fan (Regional Studies in Marine Science, 2024)

Doppler Compensation Techniques for M-Ary Sequence Spread Spectrum Signals Based on Correlation Cost Factors in Mobile Underwater Acoustic Communication - Yubo Han; Shuping Han; Heng Zhao; Yaohui Hu; Jingfeng Xu; Gang Yang (Journal of Marine Science and Engineering, 2024)
Unlike terrestrial radio, the speed of sound in the ocean is relatively slow, which results in mobile underwater M-ary spread spectrum communication typically exhibiting significant and variable multipath effects along with strong Doppler effects, leading to rapid carrier phase shifts in the received signal that severely impact decoding accuracy. This study aims to address the issue of rapid carrier phase shifts caused by significant time-varying Doppler shifts during mobile underwater M-SS communication. This paper innovatively proposes a method for updating matched filters based on correlation cost factors. By calculating the correlation cost factors for each received symbol, the method guides the direction of Doppler estimation and updates the matched filters. After identifying the optimal match, the received symbols are shifted, correlated, and decoded. Simulation and sea trial results indicate that this method demonstrates higher computational efficiency and improved decoding accuracy compared to traditional Doppler estimation matched filters under low signal-to-noise ratio conditions, and exhibits greater robustness under complex motion conditions.

PGE2 Overexpressing Human Embryonic Stem Cell Derived Mesenchymal Stromal Cell Relieves Liver Fibrosis in an Immuno-suppressive Manner - Yan Zhong; Xiaohao Hu; Jingfeng Liu (Stem Cell Reviews and Reports, 2024)

Co-exposure with cadmium elevates the toxicity of microplastics: Trojan horse effect from the perspective of intestinal barrier - Liehai Hu; Xiaoyan Feng; Yuzhi Lan; Jingfeng Zhang; Penghui Nie; Hengyi Xu (Journal of Hazardous Materials, 2024)

Long-term response of the microbial community to the degradation of DOC released from Undaria pinnatifida - Yuyang Xie; Jie Su; Kuishuang Shao; Tian Hu; Hongxia Ming; Tingting Shi; Wenjing Wang; Jingfeng Fan (Marine Environmental Research, 2024)

Plant community diversity alters the response of ecosystem multifunctionality to multiple global change factors - Zhenwei Xu; Xiao Guo; Warwick J. Allen; Xiaona Yu; Yi Hu; Jingfeng Wang; Mingyan Li; Weihua Guo (Global Change Biology, 2024)
Biodiversity is considered important to the mitigation of global change impacts on ecosystem multifunctionality in terrestrial ecosystems. However, potential mechanisms through which biodiversity maintains ecosystem multifunctionality under global change remain unclear. We grew 132 plant communities with two levels of plant diversity, crossed with treatments based on 10 global change factors (nitrogen deposition, soil salinity, drought, plant invasion, simulated grazing, oil pollution, plastics pollution, antibiotics pollution, heavy metal pollution, and pesticide pollution). All global change factors negatively impacted ecosystem multifunctionality, but negative impacts were stronger in high compared with low diversity plant communities. We explored potential mechanisms for this unexpected result, finding that the inhibition of selection effects (i.e., selection for plant species associated with high ecosystem functioning) contributed to sensitivity of ecosystem multifunctionality to global change. Specifically, global change factors decreased the abundance of novel functional plants (i.e., legumes) in high but not low diversity plant communities. The negative impacts of global change on ecosystem multifunctionality were also mediated by increased relative abundance of fungal plant pathogens (identified from metabarcoding of soil samples) and their negative relationship with the abundance of novel functional plants. Taken together, our experiment highlights the importance of protecting high diversity plant communities and legumes, and managing fungal pathogens, to the maintenance of ecosystem multifunctionality in the face of complex global change.

The complexity of heatwaves impact on terrestrial ecosystem carbon fluxes: Factors, mechanisms and a multi-stage analytical approach - Lu-Ping Qu; Jiquan Chen; Jingfeng Xiao; Hans J. De Boeck; Gang Dong; Shi-Cheng Jiang; Ya-Lin Hu; Yi-Xuan Wang; Chang-Liang Shao (Environmental Research, 2024)

A comprehensive review of calcium and ferrous ions chelating peptides: Preparation, structure and transport pathways - Qiaoji Tian; Yan Fan; Li Hao; Jie Wang; Chensi Xia; Jingfeng Wang; Hu Hou (Critical Reviews in Food Science and Nutrition, 2023)

Convergence and divergence emerging in climatic controls of polynomial trends for northern ecosystem productivity over 2000–2018 - Wenxin Zhang; Hongxiao Jin; Sadegh Jamali; Zheng Duan; Mousong Wu; Youhua Ran; Jonas Ardö; Lars Eklundh; Anna Maria Jönsson; Huaiwei Sun; Guojie Hu; Xiaodong Wu; et al. (Science of The Total Environment, 2023)

Growth of grasses and forbs, nutrient concentration, and microbial activity in soil treated with microbeads - Jingfeng Wang; Xiao Guo; Janice Brahney; Zhenwei Xu; Yi Hu; Wenyi Sheng; Yanni Chen; Mingyan Li; Weihua Guo (Environmental Pollution, 2023)

Development of hysteretic model for LEM-filled CFS shear walls under cyclic loading - Wanqian Wang; Jingfeng Wang; Lei Guo; Peifang Hu (Engineering Structures, 2023)

Anti-rolling analysis and resistance optimization of a new anti-rolling hydrofoil for the trimaran vessel - Yihan Zhang; Jingfeng Hu; Shan Ma; Ping Wang (Ocean Engineering, 2023)

Intermittent ultrasound retains cellulases unlock for enhanced cellulosic ethanol with high-porosity biochar for dye adsorption using desirable rice mutant straw - Zhen Hu; Qian Li; Yuanyuan Chen; Tianqi Li; Youmei Wang; Ran Zhang; Hao Peng; Hailang Wang; Yanting Wang; Jingfeng Tang; Muhammad Nauman Aftab; Liangcai Peng (Bioresource Technology, 2023)

Recent advance in the investigation of aquatic “blue foods” at a molecular level: A proteomics strategy - Yanchao Wang; Yaoguang Chang; Hu Hou; Jingfeng Wang; Changhu Xue (Trends in Food Science & Technology, 2023)

Prevalence, antibiotic and heavy metal resistance of Vibrio spp. isolated from the clam Meretrix meretrix at different ages in Geligang, Liaohe estuary in China - Jie Su; Yingxue Zhang; Tian Hu; Hongxia Ming; Yuyang Xie; Yuan Jin; Tingting Shi; Jingfeng Fan (Frontiers in Marine Science, 2022)
Vibrio as one of the main pathogens of shellfish diseases can cause serious human seafoodborne gastroenteritis and even death. In this study, we analyzed the bacterial communities from the clam, and compared the resistance phenotypes and genotypes of Vibrio spp. from Meretrix meretrix at different growth stages. High-throughput sequencing analysis revealed the predominance of Proteobacteria (50%) in the bacterial community and Vibrio was one of the dominant genera in the clam hepatopancreas in the summer. Vibrio abundance in Meretrix meretrix positively correlated with the water temperature (p<0.05). A total of 73 Vibrio isolates from Meretrix meretrix were classified into 19 species and the dominant strains included V. mediterranei (19%) and V. harveyi (11%), V. algolyticus (10%), and V. parahaemolyticus (8%). The species and abundance of Vibrio spp. were the highest in the 3-year-old of Meretrix meretrix compared with clams of other ages in the summer. Among the 73 isolates, 68 Vibrio strains were resistant to other 15 antibiotics except for sulfamethoxazole-trimethoprim with 57 resistant phenotypes. The most prevalent resistance was toward clindamycin (76%), followed by amikacin (63%), ampicillin (62%), rifampicin (62%), vancomycin (57%), and amoxicillin (50%). The ARI values of Vibrio spp. in different ages ranged from 0.13 to 0.18, and ARI values of 3-year-old (ARI=0.18) clams are higher than that of other ages clam. Approximately 72% of the resistant isolates showed multidrug-resistant phenotypes with maximum resistance to 15 antibiotics. Tolerance to heavy metals including Cd, Zn, and Cu was detected in the majority of antibiotic resistant isolates. In addition to the co-resistance to the same class of antibiotics, resistance to cephalosporin (CFP, CEP, CZ) were significantly correlated with penicillins (AMP, AMC) ( p < 0.01), tetracycline ( p < 0.001), sulfanilamide (SXT) ( p < 0.01) and quinolone (CIP) ( p < 0.01). The heavy metal resistance genes copB and nccA were significantly correlated with the clindamycin resistance phenotype ( p <0.01). This study revealed that the habitat of Meretrix meretrix is in low exposure to antibiotics, and a link between heavy metal resistance genes and antibiotic resistance.

Spatio-temporal evolution and future scenario prediction of karst rocky desertification based on CA–Markov model - Fei Chen; Shijie Wang; Xiaoyong Bai; Fang Liu; Yichao Tian; Guangjie Luo; Qin Li; Jingfeng Wang; Luhua Wu; Yue Cao; Huiwen Li; Yuanhong Deng; et al. (Arabian Journal of Geosciences, 2021)

Isolation and genomic characterization of a pathogenic Providencia rettgeri strain G0519 in turtle Trachemys scripta - Minghao Ye; Xiucai Hu; Aijun Lü; Jingfeng Sun; Chengxun Chen (Antonie van Leeuwenhoek, 2020)

Skin transcriptome, tissue distribution of mucin genes and discovery of simple sequence repeats in crucian carp ( Carassius auratus ) - Jie Bai; Xiucai Hu; Aijun Lü; Ruixia Wang; Rongrong Liu; Jingfeng Sun; Yuchen Niu (Journal of Fish Biology, 2020)
Crucian carp ( Carassius auratus ) is one of the major freshwater species and important food fish in China. Fish skin acts as the first line of defence against pathogens, yet its molecular and immune mechanism remains unclear. In this study, a de novo transcriptome assembly of C. auratus skin was performed with the Illumina Hiseq 2000 platform. A total of 49,154,776 clean reads were assembled, among which 60,824 (46.86%), 37,103 (28.59%), 43,269 (33.33%) unigenes were annotated against National Center for Biotechnology Information, Gene Onotology and Kyoto Encyclopedia of Genes and Genomes (KEGG) databases, respectively. KEGG Orthology categories were significantly involved in immune system (20.50%), signal transduction (18.04%) and mucosal mucin genes ( e.g. , muc2 , muc5AC , muc5B , muc17 , muc18 ). The high expression of muc18 gene was observed in brain; that of muc2 in intestine; and that of muc5AC in skin, liver, spleen, intestine and muscle. Moreover, the potential 28,928 simple sequence repeats with the three most abundant dinucleotide repeat motifs (AC/GT, AG/CT, AT/AT) were detected in C. auratus . To authors’ knowledge, this is the first report to describe the transcriptome analysis of C. auratus skin, and the outcome of this study contributed to the understanding of mucosal immune response of the skin and molecular markers in cyprinid species.

First report on the characterization of pathogenic Rahnella aquatilis KCL‐5 from crucian carp: Revealed by genomic and proteomic analyses - Jing Liang; Xiucai Hu; Aijun Lü; Jingfeng Sun (Journal of Fish Diseases, 2020)
Rahnella aquatilis is an important pathogen of several aquatic organisms and is found widely distributed in the freshwater, soil, fish and human clinical samples. Our previously published study reported a novel pathogenic R. aquatilis strain KCL‐5 to crucian carp ( Carassius auratus ). To further investigate the characteristics and pathogenesis caused by R. aquatilis , we here report on the pathological changes, bacterial genomic and proteomic analyses of strain KCL‐5. Significantly pathological changes in liver, intestine, spleen and gills were observed in infected fish. The genome consists of one circular chromosome 5,062,299 bp with 52.02% GC content and two plasmids (506,827 bp, 52.16%; 173,433 bp, 50.00%) and predicted 5,653 genes, 77 tRNAs and 22 rRNAs. Some virulence factors were characterized, including outer membrane protein, haemolysin, RTX toxin, chemotaxis and T3SS secretion system. Antimicrobial resistance genes such as EmrAB‐TolC, MexABC‐OpmB and RosAB efflux pump were found in strain KCL‐5. KEGG analysis showed that mainly functional modules were ABC transporters, biosynthesis of amino acids, two‐component system, quorum sensing, flagellum assembly and chemotaxis, in which most of them were identified by using 2‐DE/MS analyses. To our knowledge, this was first report on the molecular characteristics of R. aquatilis by multi‐omics approaches, which will provide insights into the pathogenic mechanism of R. aquatilis infection in fish.

Detection and characterization of Aeromonas salmonicida subsp. salmonicida infection in crucian carp Carassius auratus - Zhengyi Lian; Jie Bai; Xiucai Hu; Aijun Lü; Jingfeng Sun; Yongjun Guo; Yajiao Song (Veterinary Research Communications, 2020)

A deep learning approach to conflating heterogeneous geospatial data for corn yield estimation: A case study of the US Corn Belt at the county level - Hao Jiang; Hao Hu; Renhai Zhong; Jinfan Xu; Jialu Xu; Jingfeng Huang; Shaowen Wang; Yibin Ying; Tao Lin (Global Change Biology, 2020)
Understanding large‐scale crop growth and its responses to climate change are critical for yield estimation and prediction, especially under the increased frequency of extreme climate and weather events. County‐level corn phenology varies spatially and interannually across the Corn Belt in the United States, where precipitation and heat stress presents a temporal pattern among growth phases (GPs) and vary interannually. In this study, we developed a long short‐term memory (LSTM) model that integrates heterogeneous crop phenology, meteorology, and remote sensing data to estimate county‐level corn yields. By conflating heterogeneous phenology‐based remote sensing and meteorological indices, the LSTM model accounted for 76% of yield variations across the Corn Belt, improved from 39% of yield variations explained by phenology‐based meteorological indices alone. The LSTM model outperformed least absolute shrinkage and selection operator (LASSO) regression and random forest (RF) approaches for end‐of‐the‐season yield estimation, as a result of its recurrent neural network structure that can incorporate cumulative and nonlinear relationships between corn yield and environmental factors. The results showed that the period from silking to dough was most critical for crop yield estimation. The LSTM model presented a robust yield estimation under extreme weather events in 2012, which reduced the root‐mean‐square error to 1.47 Mg/ha from 1.93 Mg/ha for LASSO and 2.43 Mg/ha for RF. The LSTM model has the capability to learn general patterns from high‐dimensional (spectral, spatial, and temporal) input features to achieve a robust county‐level crop yield estimation. This deep learning approach holds great promise for better understanding the global condition of crop growth based on publicly available remote sensing and meteorological data.

Angiotensin II induces apoptosis of cardiac microvascular endothelial cells via regulating PTP1B/PI3K/Akt pathway - Yanyan Wang; Yuyuan Fan; Yu Song; Xueting Han; Mingqiang Fu; Jingfeng Wang; Xiaotong Cui; Juan Cao; Li Chen; Kai Hu; Aijun Sun; Jingmin Zhou; et al. (In Vitro Cellular & Developmental Biology - Animal, 2019)

Tissue distribution of olive flounder VDAC2 and its expression in fish cell lines - Aijun Lü; Xiucai Hu; Li Li; Chao Pei; Chao Zhang; Xianglin Cao; Xianghui Kong; Guoxing Nie; Xuejun Li; Jingfeng Sun (Fish Physiology and Biochemistry, 2015)

Differences in sex reversion and growth between normal and neomale stock in half-smooth tongue sole, Cynoglossus semilaevis - Qiaomu Hu; Song-Lin Chen; Fengtao Gao; Yangzhen Li; Shanshan Liu; Feng Liu; Jingfeng Yang; Min Du (Aquaculture International, 2014)

Hpyerglycemic effect of a mixture of sea cucumber and cordyceps sinensis in streptozotocin-induced diabetic rat - Shiwei Hu; Jingfeng Wang; Zhaojie Li; Jia Fu; Yuming Wang; Changhu Xue (Journal of Ocean University of China, 2014)